The voluntary sector in welfare: understanding the factors that have influenced its development in Cyprus from the mid-end colonial period to the present - Patsalidou, Olivia (2014)
In the long history of Cyprus, the ‘persona’, contributions, underpinning ideologies, role and historical trajectory of the voluntary sector, have not, unlike in other countries, been the subject of any substantial empirical and theoretical exploration, remaining under-researched questions. The main purpose of the research is to understand the rich past of the Cypriot voluntary sector and trace its trajectory to the present. How and why did the voluntary sector develop? Which factors lie behind its development?